Twin towers: A philosophy and theology of business - Byron, William J. (Journal of business ethics, 1988)
To be in business is first to be. To do in business, is to enhance one's being and the being of others; it ought never result in the diminishment of either. This article invites philosophical reflection on the purpose of business., To be and do in business looks for an explanation that goes beyond the meaning of work. The meaning of work is a worthy philosophical inquiry; the meaning of business is a separate question. The purpose of business is relational. Business is doing for others on condition of receipt of something of fair value in return. It deals essentially with exchanges. Persons in business relate to other persons whose needs, preferences, and desires are met, to some degree of satisfaction, by the product or service the business is organized to provide — at a price. To meet the need, preference or desire is the purpose of business., Theology, through the categories of creation and stewardship, sheds additional light on the purpose of business. There is theological significance in the human action of making available, through fair exchanges, the goods and services people need, prefer and, in some cases, simply desire. There is also theological meaning in the managerial and entrepreneurial function of making employment available for others, thus helping them to be more active and productive human beings. From a theological perspective, the purpose of business activity is to serve a people on the way to salvation by organizing the material basis of their transit through life.